The agency of the forum: Mechanisms for algorithmic accountability through the lens of agency - Florian Cech (Elsevier, 2021)
The wicked challenge of designing accountability measures aimed at improving algorithmic accountability demands human-centered approaches. Based on one of the most common definitions of accountability as the relationship between an actor and a forum, this article presents an analytic lens in the form of actor and forum agency, through which the accountability process can be analysed. Two case studies - the Austrian Public Employment Service’s AMAS system and the EnerCoach energy accounting system, serve as examples to an analysis of accountability based on the agency of the stakeholders. Developed through the comparison of the two systems, the Algorithmic Accountability Agency Framework (A3 framework) aimed at supporting the analysis and the improvement of agency throughout the four steps of the accountability process is presented and discussed.